MINORITY RECRUITMENT - Mahdi, Sahed (Jurnal Mentari, 2009)
Keberadaan tenaga kerja unggul dalam sebuah perguruan tinggi menjadi tolak ukur keberhasilan kampus dalam jangka panjang. Karyawan atau staff pengajar yang unggul bisa menjadikan nilai competitive bagi sebuah perguruan tinggi, di mana para pesaing sulit untuk meniru keunggulan tersebut dalam jangka pendek. Oleh karena itu, dalam article ini menjelaskan model dan kebijakan perkrutan karyawan dalam industri perguruan tinggi Amerika, terutama untuk tenaga pengajar dari golongan minoritas.. Disamping itu, artikel ini juga menjelaskan hubungan positif yang di kaitkan dengan aspek hukum  dalam bidang ketenaga kerjaan dengan process seleksi tenaga pengajar dari golongan minoritas.yang di harapkan bisadi implementasikan dalam dunia perguruan tinggiAceh.     The existence of labor excel in a college campus become the benchmark of success in the long run. Employees and faculty can make superior competitive value for a college, where the competitors is difficult to replicate these advantages in the short term. Therefore, in this article describes the models and policies perkrutan employees in American college industry, especially for teachers from minority groups .. In addition, this article also explains the positive relationship in associate with aspects of employment law in the field with the selection process of teachers is expected bisadi minoritas.yang class implemented in the world of college tinggiAceh. Keywords: Minority recruitment, affirmative action and faculty recruitment.   References American Association of State Colleges and Universities (2006).  Faculty Trends and Issues.  Retrieved: November 12, 2008.  www.aascu.org. Association of American Colleges and Universities (2006).  Peter D. Hart Research Associates, Inc.  How Should Colleges Prepare Students to Succeed in Today’s Global Economy? Retrieved: November 10, 2008.  www.aacu.org. Auburn University Office of Affirmative Action/EEO.  Faculty Recruitment Checklist.  Retrieved: November 11, 2008. http://www.auburn.edu/administration/aaeeo/. Auburn University AA/EEO Major Laws.  Retrieved: November 12, 2008. http://www.auburn.edu/administration/aaeeo/majorlaws/constitution.html. Bernard, Pamela J. (2006).  When Seeking a Diverse Faculty, Watch Out for Legal Minefields.  The Chronicle of Higher Education. 53 (6). Jaschik, Scott. (2006).  New Approaches to Faculty Hiring.  Inside Higher Ed. Retrieved: November 12, 2008.  http://www.insidehighered.com. Kennedy, John F. (1961).  Establishing the President’s Committee on Equal Employment Opportunity.  Executive Order 10925.  Retrieved: November 11, 2008. National Center for Education Statistics (2008).  Digest of Educational Statistics: 2007. Retrieved: November 12, 2008. http://nces.ed.gov. Penn State University Budget Office.  Retrieved: November 20, 2008. http://www.budget.psu.edu. Steele, Bill (2006).  In a Seller’s Market, Cornell Needs to Recruit Hundreds of New Faculty, Putting Years-long Pressure on Budget.  Retrieved: November 18, 2008. http://www.news.-cornell.edu/stories/Oct06/DC.faculty.ws.html. The U.S. Equal Employment Opportunity Commission (2008).  Race/Color Discrimination.  Retrieved: November 12, 2008.  http://www.eeoc.gov/types/race.html. Turner, Caroline. (2002). Diversifying the Faculty: A Guidebook for Search Committees. Washington, DC: Association of American Colleges and        Universities. University of Michigan Human Resources.  Retrieved: November 13, 2008. http://www.hr.umich.edu. U.S. Census Bureau (2008). An Older and More Diverse Nation by Midcentury. Retrieved: November 12, 2008.  http://www.census.gov. Wheeler, David L. (2008).  Colleges Explore New Ways to Manage Retirements.  The Chronicle of Higher Education. 54 (40). Wilson, Robin (2002).  Stacking the Deck for Minority Candidates?  The Chronicle Of Higher Education. 48 (44).